Health and Safety Issues of Industry Workmen - Siddiqui, F.; Akhund, M. A.; Memon, A. H.; Khoso, A. R.; Imad, H. U. (Engineering, Technology & Applied Science Research, 2018)
Flour milling is considered the oldest trade industry, initiated at least 6000 years ago. Like every other industry, numerous problems arise during functioning and maintenance operations. The production process involves the breakdown of grains to separate their outer covering and inner endosperm grinding to fine flour particles. Workers serving in the industry have been in an environment exposed to flour dust. After conducting several interviews and a questionnaire survey to the workers and sales managers of flour mills within Hyderabad in Pakistan, the workforce was found to be suffering from sensitization, occupational asthma, allergic rhinitis, obstructive lung diseases and eye infection. The core reason was the inhaled and swallowed flour dust. The majority of the respondents highlighted improper flour milling process including intake and final product collection systems as the main causes of these health problems. The other part of the research work revealed that the majority of safety issues emerged due to the unavailability, the failure to use and the unawareness of personal protective equipment. Regarding the suggestions received during the survey from respective stakeholders, the health and safety issues can be controlled by improving feeding and collection systems and by wearing personal protective equipment.